PELATIHAN HOSPITALITY: MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA AGROWISATA BUMI MANDIRI JAYA SEHINGGA MENJADI PARIWISATA BERKELANJUTAN DI KABUPATEN PRINGSEWU - Revirani, Selvie; Lefiani, Nia; Lyntang, Dwi Abraham (LPPM Universitas Bina Bangsa, 2025)
Tourism is one of the influential factors in the economy of a country. Indonesia is one of the destination countries for tourists, both foreign tourists and domestic tourists. Tourism can also have a big impact on the surrounding area, for example in terms of job opportunities. The quality of skilled human resources in the tourism sector is very much needed in advancing the tourism sector. Tourism is also closely related to hospitality, because the tourism sector is related to the service sector. In this community service activity carried out at Bumi Mandiri Jaya Agrotourism which is located at Wonodadi, Gading Rejo District, Pringsewu Regency, Lampung, training will be provided on hospitality, handling tourist complaints and tourism marketing with the hope of increasing skilled human resources in the field tourism, quantity and quality of the surrounding community as well as advancing the community's economy in Bumi Mandiri Jaya Agrotourism so that it becomes sustainable tourism in Pringsewu Regency. This activity has great benefits for the owners, managers and human resources at Bumi Mandiri Jaya Agrotourism.